Larval sites of the mosquito Aedes aegypti formosus in forest and domestic habitats in Africa and the potential association with oviposition evolution - (:unkn) unknown (My University, 2021)
Adaptations to anthropogenic domestic habitats contribute to the success of the mosquito Aedes aegypti as a major global vector of several arboviral diseases. The species inhabited African forests before expanding into domestic habitats and spreading to other continents. Despite a well-studied evolutionary history, how this species initially moved into human settlements in Africa remains unclear. During this initial habitat transition, African Ae. aegypti switched their larval sites from natural water containers like tree holes to artificial containers like clay pots. Little is known about how these natural versus artificial containers differ in their characteristics. Filling this knowledge gap could provide valuable information for studying the evolution of Ae. aegypti associated with larval habitat changes. As an initial effort, in this study, we characterized the microenvironments of Ae. aegypti larval sites in forest and domestic habitats in two African localities: La Lopé, Gabon, and Rabai, Kenya. Specifically, we measured the physical characteristics, microbial density, bacterial composition, and volatile chemical profiles of multiple larval sites. In both localities, comparisons between natural containers in the forests and artificial containers in the villages revealed significantly different microenvironments. We next examined whether the between-habitat differences in larval site microenvironments lead to differences in oviposition, a key behavior affecting larval distribution. Forest Ae. aegypti readily accepted the artificial containers we placed in the forests. Laboratory choice experiments also did not find distinct oviposition preferences between forest and village Ae. aegypti colonies. These results suggested that African Ae. aegypti are likely generalists in their larval site choices. This flexibility to accept various containers with a wide range of physical, microbial, and chemical conditions might allow Ae. aegypti to use human-sto
Keywords: African Research